REPRESENTASI HEDONISME DAN KEKERASAN DALAM FILM "THE MENU" (Analisis Semiotika Roland Barthes) - Nafia Marvelin, (2024)
The purpose of this research is depicting a representation of hedonism and violence found in the movie "The Menu", directed by Mark Mylod. This research data is analyzed using the semiotics analysis method by Roland Barthes which uses two-stages of significance models, denotation, connotation, and myth. The movie tells the story of a group of VIP guests who travel to a remote island to enjoy a meal at a luxury restaurant named Hawthorne, run by a celebrity chef, Julian Slowik. Unexpectedly, the dinner brought them shocking experience of tortures and abuses from Slowik and all Hawthorne employees. Apparently, the dinner is a part of Slowik's revenge mission to the upper class guests who disrespect his artwork and contribute to the loss of Slowik's passion as a chef. The approach used in this study is descriptive qualitative with data obtained through observations and documentation on the movie's scenes. The result of this research prove that representations of hedonism and violence in the movie "The Menu" evidenced by the presence of signs of hedonism and violence contained in several scenes. The forms of hedonism found include a life that is oriented towards success and money, doing things only for the sake of prestige, having a high consumer behavior and belief that power can solve various problems, while the forms of violence found are physical / direct violence aimed at ending lives such as shooting, stabbing, cutting off body parts, drowning and burning people alive and verbal / emotional violence in the form of terror, threats and intimidation. Whether visualized in pictures or dialogues.